1996
DOI: 10.1089/hum.1996.7.4-463
|View full text |Cite
|
Sign up to set email alerts
|

Selective Killing of AFP-Positive Hepatocellular Carcinoma Cells by Adeno-Associated Virus Transfer of the Herpes Simplex Virus Thymidine Kinase Gene

Abstract: The use of viral thymidine kinase (TK) gene coupled with the administration of ganciclovir to render cancer cell death has been studied extensively. Many of these experiments utilized retrovirus to transfer the TK gene under the control of a nonspecific promoter. Because nonspecific expression of the viral TK gene may cause death of proliferating cells, other than cancer cells, we explored the use of a liver-specific promoter and a tumor-specific AFP enhancer to achieve regulated viral TK gene expression for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 16 publications
1
43
0
2
Order By: Relevance
“…It has been demonstrated that gene expression of highly efficient gene therapy vectors can be targeted to tumors using cell-type or tissue-type specific promoter elements. [6][7][8][9][10][11][12] Most of these tumor-specific promoters, however, are relatively weak resulting in insufficient transgene expression levels. Several studies have reported that a CEA promoter driving a prodrug gene could mediate selective gene expression in CEA-producing tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that gene expression of highly efficient gene therapy vectors can be targeted to tumors using cell-type or tissue-type specific promoter elements. [6][7][8][9][10][11][12] Most of these tumor-specific promoters, however, are relatively weak resulting in insufficient transgene expression levels. Several studies have reported that a CEA promoter driving a prodrug gene could mediate selective gene expression in CEA-producing tumors.…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, adenoassociated viruses were used that express HSV-TK from an AFP or albumin promoter and were shown to selectively inhibit growth of HCC cells in vitro as well as in vivo. 30,31 Even interleukin 2 expressing adenoviral vectors containing the AFP promoter were capable of selective growth retardation of human HCC xenografts in SCID mice. 32 Adenoviral vectors are highly efficient for in vivo gene transfer into a variety of tissues and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been evidenced by osteocalcin 8 and thyroglobulin 9 promoters for osteosarcoma and thyroid tumors, respectively. Another approach is to use the regulatory sequences of oncofetal protein such as -fetoprotein and carcinoembryonic antigen to express foreign genes in hepatic tumors 10,11 and tumors of the digestive tract, 12,13 respectively. Although the gene expression with the cell typespecific promoters is strictly regulated, the promoter activity could not be as strong as that with the promoters of oncofetal protein genes.…”
Section: Discussionmentioning
confidence: 99%